193k views
2 votes
Anyone know answer ???

Anyone know answer ???-example-1
User Lordian
by
4.8k points

1 Answer

4 votes

Answer:

C

Explanation:

We know that ∠ 1 + ∠ 2 + ∠3 = 180 → (1)

and ∠ 3 + ∠ 4 = 180 → (2)

From (2) ∠ 3 = 180 - ∠ 4

Substitute ∠ 3 = 180 - ∠ 4 into (1)

∠ 1 + ∠ 2 + 180 - ∠ 4 = 180 ( add ∠ 4 to both sides )

∠ 1 + ∠ 2 + 180 = 180 + ∠ 4 ( subtract 180 from both sides )

∠ 1 + ∠ 2 = ∠ 4 → C

User Dyp
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.